KOSMOLOGI HINDU DALAM BHAGAVADGĪTĀ - I Made Gami Sandi Untara (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Hindus have a holy book, the Vedas, which are the guidelines for human life in every process of life, which gives enlightenment to life. One of them is Bhagavadgītā. Bhagavadgītā also learned about precept as manifestation of the universe. Hindu cosmology teaches about the origin of the creation and development of the universe by placing God, also called the Soul of the Universe, as the origin of the universe. Hindu cosmology is different from general cosmology studied by Western scientists, Hindu cosmology deliberately and consciously places God as the beginning, middle and end of the existence of the cosmos, while cosmology in general (Western) is not too important to place and involve God. The process of creation in the Bhagavadgītā begins with the most subtle form to the crudest form. It starts with the emptiness of the mind in the sphere of garbha (God's content). Then comes the element of consciousness (budhi), followed by the power of creation (mind), so that an element of self (ahamkara) appears, then five gross elements (Panca Maha Butha) are formed. The first creation of Panca Maha Butha is akasa (ether), followed by bayu (air), teja (fire), apah (water), and prathivi (land).Keywords: Hindu cosmology, Bhagavadgītā